2004
DOI: 10.1590/s1517-83822004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Antimycobacterial activity of the antiinflammatory agent diclofenac sodium, and its synergism with streptomycin

Abstract: Diclofenac sodium, an antiinflammatory agent, exhibited remarkable inhibitory action against both drug sensitive and drug resistant clinical isolates of Mycobacterium tuberculosis, as well as other mycobacteria. This drug was tested in vitro against 45 different strains of mycobacteria, most of which were inhibited by the drug at 10-25 µg/ml concentration. When tested in vivo, diclofenac, injected at 10 µg/g body weight of a Swiss strain of white mice, could significantly protect them when challenged with 50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…According to Dutta et al (2004) antimycobacterial activity was determined by diffusion technique in Lowenstein Jensen medium (LJM). Distilled water (1.5 mL) was added to lyophilized extracts and filtered with a 0.22 µm membrane.…”
Section: Methodsmentioning
confidence: 99%
“…According to Dutta et al (2004) antimycobacterial activity was determined by diffusion technique in Lowenstein Jensen medium (LJM). Distilled water (1.5 mL) was added to lyophilized extracts and filtered with a 0.22 µm membrane.…”
Section: Methodsmentioning
confidence: 99%
“…A survey conducted by United Nations Conference on Trade and Development (UNCTAD)-General Agreement on Tariffs and Trade (GATT) showed that 33% of total drugs produced by pharmaceutical industries are derived from plants and microbes, 60% of medicinal products are natural origin (Srinivasan et al, 2001). Some traditional orthodox anti-inflammatory agents have been demonstrated to exhibit antibacterial activity (Annadurai et al, 1998;Dutta et al, 2004) and hence any bioactive agent possessing both properties may be beneficial to patients especially those suffering from acute inflammation and bacterial infections at the same time. Some medicinal and pharmacological values have been observed in different species of Cola (DaelsRakotoarison et al, 2003;Steinegger & Hansel, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…After incubation at 37ºC, for 24 h, the inhibitory concentrations of each substance were assessed. The absence of cellular growth and viability was determined as previously described [20,21].…”
Section: Antimicrobial Interactions: Checkerboard Methodsmentioning
confidence: 99%
“…Resulting values were interpreted as the following: synergistic (FICI < 0.5), additive (0.5 < FICI < 1.0), indifferent (1.0 < FICI < 4.0), or antagonist (FICI > 4.0) [21,22].…”
Section: Antimicrobial Interactions: Checkerboard Methodsmentioning
confidence: 99%